Increased velocity at VO2max and load carriage performance in army ROTC cadets: prescription using the critical velocity concept. Issue 6 (3rd June 2021) - Dicks, Nathan D.; Mahoney, Sean J.; Kramer, Mark; Lyman, Katie J.; Christensen, Bryan K.; Pettitt, Robert W.; Hackney, Kyle J.
Abstract: The purpose of this study was to evaluate the effects of using the critical velocity (CV) concept to prescribe two separate high-intensity interval training (HIT) exercise programs aimed at enhancing CV and load carriage performance. 20 young adult participants (male = 15, female = 5) underwent a 4-week training period where they exercised 2 d wk −1 . Participants were randomly assigned into two groups: (1) HIT or (2) Load Carriage-HIT (LCHIT). Pre- and post-training assessments included running 3-minute All-Out Test (3MT) to determine critical velocity (CV) and distance prime ( D ′) and two load carriage tasks (400 and 3200 m). There were significant increases in CV ( p = 0.005) and velocity at V ˙ O2max ( v V ˙ O2max ) ( p = 0.037) among the sample but not between training groups. Improvements were observed in 3200 m load carriage performance time ( p < 0.001) with a 9.8 and 5.4% decrease in the LCHIT and HIT groups, respectively. Practitioner summary: Critical velocity has shown efficacy as a marker for performance in tactical populations. With the addition of load carriage, there is a reduction in the individual's CV. The CV-concept-prescribed exercises (HIT and LCHIT) 2 days per week for 4 weeks showed improvements in CV, v V ˙ O2max and load carriage performance. The use of the CV concept provides a method to prescribe HIT to increase running and load carriage performances in tactical populations.